Coordinated improvement of maize grain yield and protein quality by the ZmMADS8-ZmMADS47-O2 module and a G protein gamma subunit - Yunfu Li; Qiang Ning; Ran Zhao; Dan Liu; Nan Li; Qing Xiong; Qin Sun; Yanfang Du; Ruijie Mao; Jimin Zhan; Zuxin Zhang; Lei Liu (Crop Journal)
Improving protein quality and grain yield traits coordinately is an important goal for crop breeding. To date, many protein-quality or grain-yield regulation genes have been identified. However, the genetic strategies integrating these genes in good-protein-quality and high-yield crop breeding practice are far from established. Here, we characterized the functions of the MADS domain-containing protein ZmMADS8 and Zea mays G protein gamma subunit 1 (ZmGG1) in regulating protein quality and grain yield of maize. ZmMADS8 positively regulates zein protein accumulation and negatively regulates non-zein protein and lysine levels in kernels by interacting with ZmMADS47 to promote the transcriptional activation of Opaque2. Additionally, ZmMADS8 regulates starch content of kernels by targeting genes involved in starch biosynthesis. ZmGG1, a putative interactor of ZmMADS8, negatively regulates kernel number with a trade-off effect on kernel starch accumulation. The mads8;zmgg1 double mutant improved protein quality by attenuating zein biosynthesis and increasing essential lysine level, and increased grain yield by increasing kernel number, compensating for decreased starch biosynthesis. Our findings revealed the biological function of ZmMADS8 and ZmGG1 in regulating protein quality and yield related traits and suggested a genetic strategy by direct editing of ZmMADS8 and ZmGG1 to improve grain yield and protein quality simultaneously.